Cultivating The Research Culture Mediated by Motivation Factors in Enhancing Teachers’ Performance in Conducting Action Research - Esturas, Maricel D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Nowadays, the Department of Education recently displayed an anticipated and overwhelming interest in developing a research culture. DepEd promoted action research and encouraged teachers to engage, thus this is timely to address the learning gaps during pandemic. With this set up, teachers ought to be involved in it to foster evidence-based practice and raise research productivity. The major objective of this study was to ascertain how the research culture and motivating elements of action research to improve teachers' research performance in the selected elementary school. The study was conducted at sixty-two schools in the division of San Pablo City using the ex post facto research design. A total of 750 elementary teachers randomly selected comprised the respondents of the study. The correlation between motivational factors and research skills and research productivity of teachers were all significantly related. The highest correlation in terms of data analysis can be seen evidently in personal satisfaction. This reveals that teachers engaged in research activities when chances are given to utilize their skills and the administration supports the presentation of research papers. The performance and research productivity of the teachers' research abilities and efforts have a significant indirect impact on the motivational variables involved in the research. The end result of this study signifies that the relationship between the research organizational culture and teacher research performance could be enhanced by improving the motivational factors and research skills.